ON THE ORGANIZATION OF THE SYSTEMATIC ANALYSIS AND PROPAGATION OF THE LEADING UNIVERSITIES' BEST PRACTICES - Elena V. Kudryashova; Natalia V. Chicherina (Высшее образование в России)
The aim of the article is to show the necessity for the analysis and dissemination of leading universities' best practices as a means of enhancing their competitiveness and increasing the effectiveness of transformation processes in higher education. The authors describe the current situation and the experience in best practices dissemination at the international and national levels; offer a range of best practices, developed by federal universities in different areas of their activities, to be disseminated through the system of in-service training.